The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/jocn.14662
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative patient handovers—Variability in perceptions of quality: A qualitative focus group study

Abstract: Health care providers need to be aware that postoperative handovers are affected by a set of factors related to internal (patient conditions, individual characteristics of clinicians involved and team composition) and external (timing and concurrency conflicts, handover structure) characteristics. These issues need to be acknowledged when procedures and routines for handover quality are designed, implemented and used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…A previous study from our research group assessing nurses' evaluations of postoperative handover quality found that the transferring and receiving nurses had different perceptions of the patient and handover situation (Reine, Ræder, et al, 2019). Different professional groups having different perceptions and focus during postoperative patient handover was reported by Randmaa et al (2017), and also a finding in a qualitative study by our research group (Reine, Rustoen, et al, 2019).…”
Section: Introductionsupporting
confidence: 79%
See 4 more Smart Citations
“…A previous study from our research group assessing nurses' evaluations of postoperative handover quality found that the transferring and receiving nurses had different perceptions of the patient and handover situation (Reine, Ræder, et al, 2019). Different professional groups having different perceptions and focus during postoperative patient handover was reported by Randmaa et al (2017), and also a finding in a qualitative study by our research group (Reine, Rustoen, et al, 2019).…”
Section: Introductionsupporting
confidence: 79%
“…Patient handover is a dynamic process (Manser et al, 2013), and the present study has described how the team responded and adapted to changes in patient condition and circumstances during the handovers observed. The practice of adapting handover to the patient and situation has been described in other clinical studies (Drach‐Zahavy et al, 2015; Rattray et al, 2019; Reine, Rustoen, et al, 2019). These findings imply that the ability to adapt the handover to the patient's condition and circumstances is important for quality, because patients' needs, team composition, preparation and workload during handovers are variable.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations